PERILAKU KONSUMEN DALAM PEMBELIAN TANAMAN HIAS DI KECAMATAN PEKALONGAN KABUPATEN LAMPUNG TIMUR - Anita Noviana; Yaktiworo Indriani; Suriaty Situmorang (Lampung University, 2014)
The objectives of this research are to determine the purchase decision process of the ornamental plants and the dominant factors on the consumer’s buying decision of ornamental plants. The research was conducted by a survey method in Sub-district of Pekalongan of East Lampung Regency. This location was chosen on purpose by considerate that there is agro tourism area namely BBI Horticulture, which is well known as the central area of the nursery and horticultural crops in Lampung. There were 75 respondents of both men and women that met the inclusion samples criteria, such as having at least an experience in buying ornamental plants. The results showed that the behavior of consumers in their purchase decision on ornamental plants through the introduction needs, information searching, alternative evaluation, purchase decision and post-purchase evaluation. There were three dominant component factors that influenced purchasing decisions of ornamental plant: the first principal component factor was named as appearance (trend and prestige), the second major components was named the exotics (color and uniqueness), and the third major components was named equivalency of price products (size and price) of ornamental plants. Keywords: consumers behavior, factor analysis, ornamental plants, purchase decision